Cognitive and behavioral engagement challenges in open and distance learning and potential solutions from artificial intelligence - Xue, Yanxing; Khalid, Fariza; Karim, Aidah Abdul (Frontiers in Education, 2025)
IntroductionOpen and Distance Learning (ODL) broadens educational access but often limits student engagement due to cognitive overload and weak self-regulation. Artificial Intelligence (AI) offers potential solutions through adaptive support.MethodsThis study employed a qualitative descriptive case study. Data from two focus group interviews, reflective reports, and LMS records were analyzed using reflexive thematic analysis and triangulation.ResultsStudents reported cognitive challenges such as processing complex content, information overload, and limited academic writing and quantitative skills, alongside behavioral challenges including procrastination, task prioritization, and difficulties with independent learning. Triangulation confirmed these patterns.DiscussionTargeted support measures such as structured study planners, writing guidance, and tailored resource recommendations can help learners strengthen self-regulation and engagement. Embedding such supports into ODL can reduce overload and sustain active participation.